A universalização da educação infantil no estado de Goiás: os desafios da Meta 1 do Plano Estadual de Educação - (:unkn) unknown (Universidade Estadual de Goiás, 2023)
The present research entitled, “The universalization for early childhood education in the state of Goiás: the challenges of Goal 1 of the State Education Plan., linked to the research line Work, State and Educational Policies, of the Graduate Program of the University State of Goiás – University Unit of Inhumas (UEG/UnU Inhumas). The object of investigation turned to a survey on the challenges for the expansion of early childhood education in Goiás, in view of the proposal for achieving Goal 1 of the PEE-GO2015-2025 in Goiás with regard to the expansion of vacancies in early childhood education. In view of this, the objective was to analyze Goal 1 of the State Education Plan of Goiás - PEE-GO 2015-2025 from the INEP indicators to show how the challenges of the expansion process of early childhood education in the territory of Goiás are settled in the period of 2009 to 2021. In this sense, an investigative path was traced to reveal the following specific objectives: projecting the challenges of expanding enrollment in Early Childhood Education and, for the fulfillment of goal 1 of the PEE-GO 2015-2025; contribute to the expansion of knowledge about the PNE, PEE and early childhood education in the state of Goiás; discuss and study the INEP data indicators that bring the distribution of enrollments, teachers, classes and teaching establishment; to reflect on the quantitative attendance of early childhood education in Brazil, the Midwest and Goiás. From the methodological point of view, the research was carried out in articulated stages, covering bibliographical research and documental research. The analysis of the literature and documents was based on a critical conception, based on the need to know and analyze the historical constitution of early childhood education in Brazil, the right to education provided for in the legislation, INEP indicators for early childhood education. Thus, the theoretical dialogue throughout the research process took place, with several scholars, such as: Bobbio (2004), Kulhmann Jr. (1998), Kramer (1992, 2011), Marcílio (1997), Azevedo (2013), Oliveira (2003), Lemos (2018), Dagnino (2004), Maudonnet (2020), Dourado (2011, 2019, 2020), Paiva (2016), Silva (2009), Machado (2022), Cury and Ferreira (2010), Duarte (2007), Araújo; Silveira; Cotrim (2013), Gatti; Ximenes,(2018), Duarte (2007), Campos e Campos (2012), Dalberio (2009), Knebel (2014), Barbosa (2005, 2008, 2014), Valdez (2002,2004), Costa (2016), Cury (1998, 2010, 2011), Saviani (2010), Braga (2017), Romanelli (1999), Horta (2010), Alves (2010), Abrucio (2010), Aguiar (2010), Didonet (2000), Rodrigues (2018), Golden; Grossi Junior; Furtado (2016), Ximenes and Grinkraut (2014), Ribeiro (2019),Corsino and Nunes (2011), Souza; Menezes (2017), Climaco (2017). Goal 1 and its constitutions with regard to access and expansion of early childhood education were investigated based on contributions from studies of documents and evaluations of the PNEs, PEEs GO, revoked after CF/ 1988. The legislative documents studied and analyzed were: CF/1988, CF-GO/ 1989, Law n° 8.068/1990, Law n° 9.394/1996,Complementary Law GO n° 26/1998, Law n° 11.274/2006, Law n° 10.172/2001, Law n° 62/2008, EC n° 59/2009, Law n° 12.796/2013, Law n° 13.005/2014, Law n° 18.969/ 2015. Concomitant were collected especially from INEP in its statistical synopsis of education. Thus, this stage of the research had its centrality in analyzing indicators of early childhood education that highlight enrollments, establishments, classes, teachers and service projection whose data collected and subsequently processed cover the period from 2009 to 2021. From this analysis, it was possible to understand that relative in achieving goal 1 of PNE 2014- 2024 and in PEE GO 2015-2025 from 2009 to 2021, there were some advances in terms of growth in enrollments, but what is established of 50% attendance for daycare centers and universalization of preschools by 2024 It is still challenging and indicates that the target will certainly not be met at the end of its term.
The universalization for early childhood education in the state of Goiás: the challenges of Goal 1 of the State Education Plan.
Keywords: Educação infantil; Meta 1; Plano Nacional de Educação; Plano Estadual de Educação de Goiás; Early childhood education; Goal 1; National Education Plan; State Education Plan; EDUCACAO::PLANEJAMENTO E AVALIACAO EDUCACIONAL